PENGARUH KONSENTRASI LARUTAN TERHADAP LAJU KENAIKAN SUHU LARUTAN - Laili Mei Ari Putri; Trapsilo Prihandono; Bambang Supriadi (JURNAL PEMBELAJARAN FISIKA, 2017)
Effect of Solution Concentration Solution Temperature Rise Against The pace of research that observing and measuring about concentration and the rate of temperature rise of the solution. A liquid will boil when the molecules gain enough energy to liberate themselves from fellow molecule that then turns into steam. When other substances dissolved in water, the substance of these substances will be particles, which later these particles would bind particles of water and escaping into vapor, in other words, the water molecules will require higher energy to boil. The time it takes to boil the solution varies depending on the size and type of solute concentration. This study aimed to investigate the relationship concentration versus time solution temperature increases 50o C, and assess the effect of concentration versus time solution temperature increases 50o C. Keywords: Effect of Solution Concentration Solution Temperature Rise Against rate